Peran Kepuasan Nasabah Deposito Memediasi Pengaruh Customer Value terhadap Loyalitas Nasabah Lembaga Perkreditan Desa (LPD) Kedonganan - Wiranata, I Kadek Putrajaya; Putu Widani Sugianingrat, Ida Ayu; Suasti Puja, I Made (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study aims to determine the role of customer satisfaction as a mediation variable that is able to mediate the influence of customer value on customer loyalty at LPD Adar Kedonganan Village in Kuta, Badung. The total population in this study was 1,040 customers where the number of samples was calculated by the slovin formula, so 91 respondents were obtained. Data collection methods by observation, interviews, literature studies and questionnaires are distributed to respondents. The data analysis techniques used are validity tests, reliability tests, descriptive tests and path analysis. The results in this study are 1) Customer value has a positive and significant effect on customer loyalty so that H0 is rejected and H1 is accepted. 2) Customer value has a positive and significant effect on customer satisfaction so that H0 is rejected and H2 is accepted. 3) Customer satisfaction has a positive and significant effect on customer loyalty so that H0 is rejected and H3 is accepted. 4) Customer satisfaction can mediate the relationship between customer value and customer loyalty where the Z value is calculated at 7.838 > 1.96. Suggestions to provide training or training for LPD employees so that when providing services to customers, customers feel happy and comfortable, and provide customers in the form of brochures or leaflets containing various products available at LPD Kedonganan Traditional Village.